Use of serum and urinary soluble sFlt-1 and PLGF in the diagnosis of preeclampsia. (2nd January 2017) - Tang, Ping; Xu, Jing; Xie, Bao-jun; Wang, Qi-mei
ABSTRACT: Objective : Preeclampsia (PE) is a disorder of pregnancy marked by hypertension and proteinuria with no known treatment aside from pregnancy termination. The pathogenesis of PE is poorly understood, but is thought to originate in the placenta. We assessed the value of measuring serum and urinary soluble deformylase-like tyrosine kinase receptor 1 (sFlt-1), a known target of placental factors, and placental growth factor (PLGF), a key placental signaling molecule, in the diagnosis of PE. Methods : Eighty patients with PE were classified as either exhibiting mild (44 cases) or severe (36 cases) symptoms of PE. Forty normal pregnant women were selected as controls. Serum and urinary PLGF and sFlt-1 levels, along with the ratio of sFlt-1 to PLGF, were compared across groups. Results : Serum and urinary sFlt-1 and sFlt-1/PLGF ratios in severe PE patients were significantly higher than those in the mild PE group, and measurements from mild PE patients were significantly higher than controls (all P values <0.01). The serum and urinary PLGF levels in severe PE patients were significantly lower than mild PE patients, and mild PE patients had significantly lower PLGF levels than controls (all P values <0.01). As expected, serum sFlt-1 and PLGF levels and ratios were highly correlated with urinary sFlt-1 and PLGF levels and ratios. Conclusions : The severity of PE was closely correlated with these measurements, suggesting that they may be useful tools in the diagnosis and evaluation of PE.